Child Mother - Kipper, Yael (Israel : JMT Films, 2016)
Elderly women who were married off as little girls recall their youth and discuss with their children their ensuing turbulent lives and their memories of lost girlhood. When they were young children and teenagers, their parents forcefully interrupted their childhood and handed them to much older men to be married. They recall the violence and fear they were subjected to, the pregnancies at the age of eleven or twelve, becoming mothers when they were still little girls themselves. It was an open secret but one they put aside forever, because revealing it might have torn their families apart. The memories of their tragic childhood never healed, they were simply suppressed for the sake of their children, their livelihoods, and their husbands.
Verzio Film Festival Submission
Keywords: Documentary films